PERKEMBANGAN TEKNOLOGI INFORMASI KOMUNIKASI (TIK), LINGKUNGAN KELUARGA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU - Marselina Lus Klarita; Lilik Sri Hariani; Naim Naim (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
This study aims to analyze: (1) the effect of the development of communication information technology, family environment and learning motivation on Integrated Social Studies learning outcomes (2) the influence of the development of communication information technology on Integrated Social Studies learning outcomes (3) the influence of family environment on Integrated Social Studies learning outcomes (4 ) the effect of learning motivation on Integrated Social Studies learning outcomes. This type of research uses ex-post-facto research using multiple linear regression. The population in this study were VII grade students of SMP Negeri 2 Kepanjen totaling 127 students, with a research sample of 56 students. The data collection technique was in the form of a questionnaire. Based on the results of the research above, the conclusion, it is known that together the development of communication information technology, family environment and learning motivation on learning outcomes, there is a significant influence on the development of communication information technology on learning outcomes, there is a significant influence on family environment on learning outcomes, and there is a significant influence of learning motivation on learning outcomes.